Short Term Reproducibility of Ambulatory Blood Pressure Monitoring in Autosomal Dominant Polycystic Kidney Disease - Rahbari-Oskoui, Frederic F. (2011)
BACKGROUND AND OBJECTIVES: Non-dipping defined as a less than 10% decline in night/day ration of blood pressure using 24 hour ambulatory blood pressure monitoring (ABPM) is associated with poor cardiovascular outcomes. However, its reproducibility has been questioned in autosomal dominant polycystic kidney disease (ADPKD). DESIGN, SETTING, PARTICIPANTS AND MEASUREMENTS: 25 of 29 recruited hypertensive or prehypertensive ADPKD patients completed ABPM on two occasions, 7–15 days apart, on a stable antihypertensive regimen. Day and night time were defined as 6:00–21:59 and 22:00–5:59. Correlation (Corr) and concordance (Conc) coefficients for systolic (SBP), diastolic blood pressure (DBP) and heart rate were determined based on night/day (N:D) and asleep/awake (A:A) periods. Consistency of dipping was assessed by using Cohen's Kappa statistics. RESULTS: Mean (±SD) for age, estimated GFR, differences in D-N night SBP and DBP were 43.12 (8.55) years, 63.1 (20.5) mL/min, 11.74(8.2) mmHg and 10.82 (6.4) mmHg respectively. 17/25 subjects (68%) and 18/25 (72%) maintained the same dipping category based on D:N or A:A separation. Cohen's Kappa was 0.34 for D:N and 0.38 for A:A ratios. Correlation and concordance coefficients were 0.89 and 0.88 for daytime SBP, 0.91 and 0.91 for daytime DBP, 0.79 and 0.78 for nighttime SBP, 0.81 and 0.80 for nighttime DBP, 0.58 and 0.56 for N:D ratio of SBP, 0.56 and 0.53 for N:D ratio of DBP. Coefficients for A:A ratios were almost identical to N:D values except for A:A ratios of SBP (0.69 and 0.67) and DBP (0.48 and 0.45). CONCLUSIONS: Repeated measures of SBP and DBP, 7–15 days apart, are highly correlative and concordant in the studied population but non-dipping, even though predominant, was found to be modestly reproducible.